Splenectomy for haematological disorders - Jankulovski, Nikola; Antovikj, Svetozar; Biljana Kuzmanovska; Mitevski, Aleksandar (Macedonian Academy of Sciences and Arts, 2014)
Splenectomy is therapeutic for a large host of conditions. It is a consequence of expanding the list of disorders and liberalizing the indications for splenectomy in many diseases. Red blood cells disorders: autoimmune hemolytic anemia, hereditary spherocytosis, hemoglobinopathies and thalassemia are prone to splenectomy after failure of medical therapy. A variety of thrombocytopenic disorders are improved by splenectomy, and the most common indication for splenectomy is ITP (idiopathic thrombocytopenic purpura). Splenectomy is successful in reversing hypersplenism in a spectrum of disease called myeloproliferative disorders. Relief of symptoms from splenomegaly is also achieved, but it does not affect the inexorable course of the disorder. The role of splenectomy in white blood cells disorders (leukemias and lymphomas) is only palliative and facilitates chemotherapy. Splenectomy in patients with hemathologic disorders imparts a risk of fulminant and life threatening infection "overwhelming postsplenectomy sepsis" that can be obviated by appropriate treatment. Although splenectomy for hemathologic disorders is only therapeutic and not curative, the relief of symptoms and for some disorders facilitation of chemotherapy leads to better quality of life and longer survival.